2013
DOI: 10.1093/neuonc/not141
|View full text |Cite
|
Sign up to set email alerts
|

Tumor targeting using magnetic nanoparticle Hsp70 conjugate in a model of C6 glioma

Abstract: The study demonstrated that Hsp70-SPION conjugate intravenously administered in C6 glioma model accumulated in the tumors and enhanced the contrast of their MR images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…a ). This result correlates well with our recently published data indicating tumor‐targeting ability of the chaperone applied intravenously with magnetic nanoparticles or administered on the surface of skin corresponding to B16 melanoma tumor area …”
Section: Discussionsupporting
confidence: 92%
“…a ). This result correlates well with our recently published data indicating tumor‐targeting ability of the chaperone applied intravenously with magnetic nanoparticles or administered on the surface of skin corresponding to B16 melanoma tumor area …”
Section: Discussionsupporting
confidence: 92%
“…Uptake of Hsp70 by tumor cells has been reported previously in models of C6 glioblastoma and B16 melanoma 14,15,43. The preferential accumulation of Hsp70 protein in C6 glioblastoma cells could be explained by CD40 receptor-mediated uptake of chaperone 44. However, the true importance of this mechanism in overall antitumor immunomodulation by Hsp70 in patients remains debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance, stress-induced mammalian Hsp70 is upregulated in T. gondii-infected cells, and inducible Hsp70 can be expressed on the cell surface (29)(30)(31)(32). While some studies reported that mammalian inducible Hsp70 is a ligand for CD40 (33,34), others could not detect binding between mammalian Hsp70 and CD40 (35)(36)(37). These contrasting results may be explained by the likely presence of contaminating proteins (Hsc70) or the source of recombinant Hsp70.…”
Section: Cd40 Restricts T Gondii Neural Invasionmentioning
confidence: 99%